Odpowiedzi

2010-03-03T18:14:45+01:00
1/3x - 2 = x+2
1/3x - x=2+2
-2/3x = 4
x=-6

x/6 - 1/6 = 1
x-1=6
x=7

3/4(2-3x)= -6
6/4 - 9/4x=-6
-9/4x=-6 - 6/4
- 9/4x = - 18/4
x=2
2010-03-03T18:16:02+01:00
1/3x - 2 = x+2
1/3x-x=2+2
-2/3x=2
x=-3

x/6 - 1/6 = 1
x/6=1+1/6
x/6=1 1/6 *6
x=14

3/4(2-3x)= -6
3-3x=-6
-3x=-6-3
-3x=-9 : (-3)
x=3
2010-03-03T18:20:20+01:00
A).1/3x - 2 = x+2
1/3x-x=2+2
-2/3=4 /*(-3/2)
x=-6

b).x/6 - 1/6 = 1
x/6=1+1/6
x/6=7/6 /*6
x=7

c).3/4(2-3x)= -6
6/4 -9/4x=-6
-9/4x=-6-6/4
-9/4x=-24/4 -6/4
-9/4x= -2/12- 9/12
-9/4x= -11/12 /*(-4/9)
x=11/27